2015
DOI: 10.1136/bjophthalmol-2015-307211
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and survival of retinoblastoma in Taiwan: a nationwide population-based study 1998–2011

Abstract: ObjectiveTo study the epidemiology of retinoblastoma in Taiwan from 1998 to 2011.DesignThis was a retrospective population-based cohort study using the Taiwan National Health Insurance Research Database.ResultsThe present study included 154 patients (92 males, 62 females) with retinoblastoma and the documented overall retinoblastoma incidence was 1 in 17 373 live births without a notable trend over the study period. The incidence per million live births examined by gender was 65.8 for males and 48.5 for female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…3,5,[16][17] Anatomical pathology examination affected the proportion of malignancy in this study as this examination is more frequently performed in cases where malignancy and visual capabilities are likely threatened. 6 Table 3 also showed that most of tumors were located in retina, which was attributed to the high number of retinoblastoma, as also found in the US. 3,5,15,18 Retinoblastoma was the most commonly found malignant tumor in this study, in agreement with the findings in the US.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…3,5,[16][17] Anatomical pathology examination affected the proportion of malignancy in this study as this examination is more frequently performed in cases where malignancy and visual capabilities are likely threatened. 6 Table 3 also showed that most of tumors were located in retina, which was attributed to the high number of retinoblastoma, as also found in the US. 3,5,15,18 Retinoblastoma was the most commonly found malignant tumor in this study, in agreement with the findings in the US.…”
Section: Discussionmentioning
confidence: 89%
“…As such, more boys receive medical attention and the mortality rates are lower among them. 6,9 Referring to the studies mentioned, cultural characteristics of a country can possibly contribute to the results of a study. In Indonesia, a tendency towards a gender has not been found, hence, the similar number of male and female patients was found in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations